Low birth weight and low mother education as dominant risk factors of stunting children in Magelang Regency, Central Java - Cati Martiyana; Anggita Mirzautika; Sri Nuryani Wahyuningrum; Ika Puspita Asturiningtyas (AcTion: Aceh Nutrition Journal, 2023)
Stunting children are still highly prevalent in Indonesia, especially in Magelang Regency, a stunting locus area. Stunting risk factors were multifactorial and closely related to maternal health and education. The study aimed to analyze the relationship between low birth weight (LBW), mother education and other risk factors with Magelang Regency stunting. This study used a case-control design and involved 328 children aged 24-59 months. The stunting group was 162 children, and the normal group was 166 children. Nutritional status was measured using median z-score height for age from WHO anthropometric standard. Children's birth weight was obtained from Maternal and Child Health books records. Other socio-demographic characteristics were obtained through interviews with mothers. The bivariate association was analyzed using Chi-square with a 95% Confidence Interval (CI). Multivariate analysis was carried out using logistic regression. The result showed that children who had a low birth weight of 7,418 higher risked being stunted (p= 0,000), and low mother education of 1,604 higher risked to be had stunted children (p= 0,041).  In conclusion, LBW and low mother education are Magelang's primary determinants of stunting.